Efektivitas Pemberian Ekstrak Marigold (Tagetes erecta L.) Komersial terhadap Bobot Telur, Bobot Komponen Telur dan Warna Yolk: Effectiveness of commercial Marigold extract on egg weight, egg component weight, and yolk color - Khaira Nova; Rr Riyanti; Dian Septinova; Teguh Rafian; Anisa Putri Cahyati; Etha 'Azizah Hasiib (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2026)
The current global challenge in the feed industry is to produce products that are both natural and functional. One potential natural ingredient is Marigold (Tagetes erecta). Marigold is rich in lutein and zeaxanthin, natural pigments and antioxidants with health benefits, and can be applied to increasing egg production in laying hens. This study aims to evaluate the effect of Marigold flower extract supplementation on egg weight, egg component weight, and yolk color in laying hens. The study was conducted experimentally using a Completely Randomized Design (CRD) with four treatments: without marigold extract (P0), 0.1 g kg-1 ration (P1), 0.2 g kg-1 ration (P2), and 0.3 g kg-1 ration (P3), each replicated five times with five hens per replication. The feed used was a commercial feed. Observed variables included egg weight, shell weight, albumen weight, yolk weight, and yolk color. Data were analyzed using analysis of variance (ANOVA), and if significant differences were found, followed by the LSD test. The results showed that Marigold extract supplementation had no significant effect on egg weight, shell weight, albumen weight, and yolk weight, but significantly increased (p<0.05) yolk color scores. Thus, it can be concluded that Marigold flower extracts play a greater role in improving the visual quality of egg yolks by increasing color intensity while enriching carotenoid content, which potentially increases the functional value of eggs as a healthy food.